Perceber emoções em (e através de) interações sociais: uma proposta deweyana - Nogueira de Carvalho, Felipe (Cognitio: Revista de Filosofia, 2022)
In our everyday interactions we can easily and effortlessly perceive emotions in others’ facial expressions and bodily behaviour. How do we do that? Philosophers and psychologists have long argued about the fundamentals of emotion perception and the debate is far from settled.While some insist on the sufficiency of morphological information contained in facial expressions, others construe the objects of emotion perception as more complex, comprising multimodal information such as touch, tone of voice, body postures, and so on. Others, in turn, have gone so far as to deny that there is a pre-given object in emotion perception in the first place, so that processes of emotion perception must be conceptualised as emergent and co-constructed phenomena in contexts of social interaction. The purpose of this paper is to argue that John Dewey’s pragmatist theory of emotions can help us make significant theoretical advancements in the understanding of emotion perception, according to which emotions are coordinated modes of behaviour that we enact with others in the contexts of social interactions. In this picture, perceiving emotions is a matter of participating in a joint activity of socio-affective coordination. This theory allows us to capture important insights that appear in these contemporary debates, while at the same time avoiding their pitfalls.